(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid advancement of Internet of Things (IoT) technology has significantly transformed the healthcare sector by enabling continuous and remote patient monitoring. This paper presents an IoT-based smart patient health monitoring system using ESP32 that efficiently tracks vital health parameters such as body temperature, blood pressure, and glucose levels in real time. The system utilizes sensors to collect physiological data, which is processed by the ESP32 microcontroller and transmitted via Wi-Fi to a Node.js-based server. The collected data is stored in a database and visualized through a web-based dashboard, allowing caregivers and medical professionals to monitor patient health remotely. Additionally, the system generates alerts when abnormal health conditions are detected, ensuring timely medical intervention. The proposed solution reduces the need for manual monitoring, improves healthcare accessibility, and enhances patient safety. Due to its low cost, scalability, and real-time capabilities, the system is highly suitable for home-based and remote healthcare applications.